Private Sector Initiatives in Forced Displacement Contexts : Constraints and Opportunities for Market-based Approaches - Wang, Weiyi (International Finance Corporation, Washington, DC, 2021)
The number of forcibly displaced persons has been rising in recent years, and many displacements have become protracted. However, public resources available to assist individuals and families have dwindled, exacerbating already strained situations. Amid this backdrop, private sector initiatives have emerged to help create jobs both for displaced people and their host communities. While market-based approaches in refugee contexts are still new, initiatives in several countries have demonstrated the valuable role that private sector firms and investors can play. This note discusses examples of these market-based initiatives, related challenges, and conflict-sensitive approaches for overcoming these challenges. The note also discusses the important role that development agencies can play in de-risking private sector development through market-creating strategies, partnerships, and blended concessional finance.